Violencia intrafamiliar en la etapa de aislamiento social en la U.E Carlos Cisneros - Carrasco Sanunga, Narcisa Paola (2021)
The intrafamily violence in the stage of social isolation is the starting point that guides the research problem. It is understood as the use of intimidation, threats, or violent behaviors that exercise power and control over another person. The social isolation stage due to the COVID-19 pandemic has increased violence, which has caused several changes in the family environment. Because of what has been previously described, the present research aimed to determine the presence of domestic violence in the situation of social isolation in third-year high school students at the U.E. Carlos Cisneros. Data collection was used based on numerical measurement and statistical analysis; for this reason, a quantitative approach was applied. The research design is non-experimental because the variables were not manipulated. It is cross-sectional because it is carried out at a certain time and only once, with a descriptive level. The sample is made up of 109 third-year high school students. The data were obtained through the application of an AD-HOC survey. Among the results, we can mention that a high percentage of students have managed to identify that in the pandemic situation, there has been an increase in intra- family violence, stating that in the stage of social isolation, good communication has been established with family members. Which could make one think about the acceptance of a relationship model based on violence.